Sel Volta Buah Mengkudu sebagai Energi Listrik Alternatif : Noni Fruit Voltaic Cells as Alternative Electrical Energy - Yusbarina (Institut Riset dan Publikasi Indonesia, 2024)
Dry cell battery which is an example of a voltaic cell is one source of energy that is widely used in everyday life. A dry cell battery consists of a cathode, anode and an electrolyte paste. In commercial dry cell batteries, electrolyte paste is made from chemicals that are harmful and can pollute the environment. Therefore, it is necessary to find an alternative electrolyte paste that does not contain harmful chemicals and has a low price. This study aims to analyze the potential of noni fruit as a conductor of electric current (electrolyte paste) in dry cell batteries. Optimization of fruit maturity, fruit processing, and the number of voltaic cells of noni fruit was carried out. A series of voltaic cells was made consisting of copper (Cu) electrodes as cathode, zinc (Zn) electrodes as anode, and noni fruit as electrolyte paste. Each variation of the voltaic cell is measured by the electrical voltage produced using a voltmeter. The best variation results are connected to a 2.5 V LED lamp to be tested for flame and longevity. From the results of the study, it was found that the voltage produced by the 14 voltaic cells of the noni fruit was 11.59 V which could turn on the 2.5 V LED lamp very brightly in 6 days of life. Noni fruit has great potential in conducting electric current and can function as a natural electrolyte in voltaic cells. Keyword: batteries, electrolyte, noni fruit, electrical energy, voltaic cell.